Essays’ Coherence Analysis Via Entity Grid Approach - Brito, Jessica Oliveira; Oliveira, Elias de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na Educação, 2023)
Coherence analysis is a challenging task, especially when applied to many domains. This paper proposes a strategy that combines Machine Learning and Linguistics to analyze text coherence by understanding entity behavior. It introduces an algorithm that automatically annotates documents based on the Entity Grid Discourse Representation. We defined two datasets, one of academic papers’ abstracts and the other of students’ essays. The annotation technique identifies the influence of grammatical structures on coherence levels and offers a cost-effective solution for coherence analysis. To assess coherence levels Machine Learning methods were used, and the experimental results demonstrate an accuracy of 88% when assessing coherence in abstracts and 74% in essays.